Basic Scientific Food Preparation Lab Manual - Department of Food Science and Human Nutrition, Iowa State University (Open textbook library., 2023)
This lab book is intended for use in both the lab and kitchen. Each section of the book contains learning objectives, lab problems to be solved, recipes, questions, and observation charts for the input of data.